Coffee Consumption and its Perceived Effects on the Study Habits of Higher Education Students - Viado, Milagros P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study describes coffee consumption and its perceived effects on the study habits of selected higher education students at Cavite State University Imus Campus. A quantitative research design was employed, surveying 208 students via a structured questionnaire. The study analyzed the data using descriptive and inferential statistics. The demographic profile of respondents shows a majority of females (55.77%) and students aged 21 to 24 years (48.07%), with most enrolled in the BSIT program. Results indicate that coffee consumption is a prevalent part of students' daily routines, with 76.44% drinking coffee daily and a significant preference for both hot and cold types (57.21%). One cup per day is the most common consumption level (57.21%). Students perceived coffee to significantly enhance cognitive functions, energy levels, productivity, and mood during study sessions, aligning with previous research highlighting caffeine's positive effects on memory, alertness, and motor coordination (Lin et al., 2023). However, there are mixed perceptions regarding dependency and withdrawal symptoms, with some negative impacts noted when coffee is not drunk, echoing concerns about tolerance and withdrawal symptoms discussed in the literature (Van De Walle et al., 2019). Findings showed no significant differences in the perceived effects of coffee consumption when the respondents were grouped by age, sex, year level, or degree program. This research suggests that coffee consumption plays a vital role in the student's academic lives. While consumption enhances cognitive and academic performance, it also presents potential risks related to coffee dependency. Administrators can use the findings of this study to enhance the school environment with a focus on food and health security by providing healthier alternatives and varied coffee options in campus canteens that can support students' academic success.